Efecto hipoglicemiante del extracto etanólico de las hojas de Bromelia pinguin - Leiva Muñoz, Lilibeth; Cassiani Reyes, Alexander; Barrios Márquez, Stefanny; Santos Bonifacio, Ketty; Camacho Romero, Oscar (Revista Médica de Risaralda, 2015)
Efecto